UPAYA GURU DALAM PENCEGAHAN TRUANCY (STUDI KASUS DI SMA NEGERI 15 PEKANBARU) - M Zulherawan; Raka Wifanjani, Gilang (UIR PRESS, 2021)
The dynamics of adolescent development today are in line with the times. The problems faced by adolescents are increasingly diverse in various aspects. Juvenile delinquency is no longer limited to skipping school or committing violations of school rules, but has spawned into criminal behavior and violence. The influence of association in shaping a person's character and personality can be a trigger for juvenile delinquency. Likewise, if parents are too restrictive, what happens is the child is unable to develop independently and they will try to break free from the restraints. But when this happens, the social environment, especially peers, is the person who is considered the most able to understand the various problems that are happening or have occurred. School is a special environment for changing behavior permanently in relation to all of his personal development. This is because most of the time for adolescents is spent in the school environment, so the character building that occurs in school must be done very carefully by teachers or educators. Therefore the authors are interested in knowing how the school's efforts to prevent truancy, especially at SMA Negeri 15 Pekanbaru. With the aim of knowing what efforts have been made by the school to prevent truancy by students. So that in this way we can know how the procedure or process is carried out by the school when truancy occurs. In addition, the author can also provide input or thoughts about how the efforts should be made by the school in preventing truancy later.